Effect of calorie-restriction and rapamycin on autophagy and the severity of caerulein-induced experimental acute pancreatitis in mice - Sharma, Manish Kumar; Priyam, Kumari; Kumar, Punit; Garg, Pramod Kumar; Roy, Tara Sankar; Jacob, Tony George (Frontiers in Gastroenterology, 2022)
Background: Impaired autophagy contributes to development of acute pancreatitis (AP). We studied the effect of inducing autophagy by calorie-restriction and rapamycin, separately, in the caerulein-induced model of severe AP. Methods: Adult, male, Swiss albino mice were given eight, hourly, intraperitoneal injections of caerulein (Ce) (50µg/Kg/dose). The interventions were calorie restriction (CR) and rapamycin (2mg/Kg). Mice were sacrificed at the 9th hour. Pancreas was harvested for histopathology and immunoblotting. Amylase activity and the levels of cytokines were measured in plasma. Results: The histopathological score and amylase activity were significantly lower in calorie-restricted caerulein-induced AP (CRCeAP) in comparison to animals that had unrestricted access to chow. In the CRCeAP group, levels of IL-6 and GM-CSF in plasma were lower and the expression of LC3II and Beclin-1 were higher. On transmission electron-microscopy, the area occupied by autophagic vacuoles was higher in CRCeAP. The expression of caspase-8 and caspase-9 was also higher in CRCeAP. In rapamycin with caerulein-induced AP (Rapa+CeAP), the histopathological score and amylase activity were significantly lower than caerulein-induced AP (CeAP). In Rapa+CeAP, the expression of LC3II and Beclin-1 were higher, whereas; SQSTM1 was decreased. The number of autophagic vacuoles in Rapa+CeAP group was fewer. Interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α) and monocyte chemoattractant protein-1(MCP-1) were lower in Rapa+CeAP. Caspase-3 increased and high mobility group box 1(HMGB1) decreased in Rapa+CeAP. Conclusion: Calorie-restriction and rapamycin can individually decrease the severity of injury in the caerulein-induced model of severe AP.